2022
DOI: 10.31234/osf.io/e6sw8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stimulus awareness is necessary for both instrumental learning and instrumental responding to previously learned stimuli

Abstract: Instrumental conditioning is a crucial part of adaptive behaviour, allowing agents to selectively interact with stimuli in their environment to maximise benefit and minimise harm. Recently accumulating evidence suggests that instrumental conditioning, such as learning to approach/avoid, cannot proceed without conscious awareness of the stimuli. However, while unconscious instrumental conditioning may not be possible, whether accurate unconscious instrumental responding can emerge from consciously acquired know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Shanks et al (2021) recommend adjusting the stimulus presentation (durations) threshold individually for each participant to ensure subliminality (Beauny et al, 2020). However, for example as demonstrated by a series of rigorous studies from Skora and colleagues (Skora et al, 2021; Skora, Livermore, Nisini, & Scott, 2022; Skora & Scott, 2022), a large number of ‘aware’ trials/participants still needs to be removed after employing such procedure.…”
Section: Methodological Issues In the Field Of Subliminal Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Shanks et al (2021) recommend adjusting the stimulus presentation (durations) threshold individually for each participant to ensure subliminality (Beauny et al, 2020). However, for example as demonstrated by a series of rigorous studies from Skora and colleagues (Skora et al, 2021; Skora, Livermore, Nisini, & Scott, 2022; Skora & Scott, 2022), a large number of ‘aware’ trials/participants still needs to be removed after employing such procedure.…”
Section: Methodological Issues In the Field Of Subliminal Processingmentioning
confidence: 99%
“…Skora, Livermore, Nisini, & Scott (2022) subsequently found differential cardiac responses towards reward/punishment feedback only in visible (but not subliminal) trials. Skora and Scott (2022) further showed that instrumental responding to subliminal cues is not possible even after learning with visible cues. Correa et al (2018), meanwhile, assessed IL with reversal learning components.…”
Section: Current Reports Of Subliminal Integrationmentioning
confidence: 99%
“…Rendering reward-and punishment-predictive stimuli subliminal (presented just under the threshold of conscious perception) through visual masking or continuous flash suppression appears to prevent the ability to learn the correct instrumental responses, in both delay and trace conditioning scenarios (Reber et al, 2018;Skora et al, 2021Skora et al, , 2022Skora et al, , 2023. What is more, even after the stimulus-action-outcome associations have been successfully learned consciously, subliminally presented stimuli fail to evoke the appropriate instrumental action to obtain reward or avoid punishments (Skora et al, 2024). Those results have been interpreted as consciousness facilitating higher-order processes, especially those requiring lasting and flexible adaptations, such as instrumental behaviour (Baars, 2002;Dehaene & Changeux, 2011;van Gaal et al, 2012;Skora et al, 2021).…”
Section: Can Non-conscious Knowledge Support Instrumental Conditioning?mentioning
confidence: 99%
“…To prevent explicit re-learning, participants won't receive feedback after every trial, but only a summation of gains and losses at the end of the phase (cf. Skora et al, 2024). We call this "the delayed instrumental responding phase".…”
Section: The Present Studymentioning
confidence: 99%